The evolving structure of Polish exports (1994-2010) – Diversification of products and trade partners - Aleksandra Parteka (Gdańsk University of Technology, Faculty of Management and Economics, 2013)
This paper presents empirical evidence on the diversification process concerning Polish exports (1994-2010), compared to European and global samples of countries. It analyzes both the commodity structure of Polish trade and the geographical diversification of Poland's trading partners. The analysis draws on highly disaggregated data on exports (HS 6digit) and combines descriptive analysis with non-parametric, semi-parametric and parametric estimation models. The results suggest that Poland (exporting 84% of all goods present in the sample) can be placed among countries with well-diversified export products. In terms of geographical diversification, Poland exploits approximately one-fifth of its theoretical overall market reach potential (the best score among new member states) and the diversification of its partner countries increased in the period analyzed. The Polish export portfolio, in terms of the variety of both its products and receiving markets, is more diversified than what is typical for countries at approximately the same stage of economic development.
Keywords: F14; F41; O11; 330; diversification; trade; export; Poland